The Ideology Of Reforming The Education Of Some Typical Reformers In Vietnam At The End Of The XIX Century, The Value Of It For The Cause Of Comprehensive Renovation Of Vietnam's Education Today - Thang, Bien Quoc (The journal of contemporary issues in business and government, 2021)
By analyzing and synthesizing methods, comparing and comparing, logic and history, the article has raised some basic problems of the current state of Vietnamese education in the late nineteenth century. Besides, the article also presents the perspectives of some reformers on contemporary education and its innovative solutions. In addition, the article has pointed out and analyzed some of the causes leading to the failed reformers' ideology of educational reform, thereby drawing lessons for the educational innovation of Vietnam today.